Antler development in reindeer in relation to age and sex - Høymork, Amund; Reimers, Eigil (Rangifer, 2002)
Yearling male and adult female reindeer (Rangifer tarandus tarandus) are similar in size and shape. If sexual clues are hidden, it can be difficult to distinguish between them. Antlers can be a useful aid in classifying yearling males and adult females, depending on whether specific antler characteristics are identifiable for these two groups. We recorded antler characteristics in a domestic reindeer herd (Vågå) and found considerable overlap in antler height, width and circumference between the different age and sex groups. Total tines and number of tine split-offs are use¬ful for the field biologist when discriminating among adult females, yearling males and 2.5 year-old males. For example, when using the tine split-offs with the suggested classification, 79% of the observed adult females and 76% of the yearling males were classified correctly. The antler height, width and circumference provide other biological dif¬ferences between groups, but are not easy to use to identify free ranging reindeer. This is due to the great overlap in antler size between the groups and measuring difficulties in a field study situation. Male and female calves have very similar antlers, and only the antler width is possible for sex discrimination, giving 67% accuracy of discriminating between these two groups.